Determining the composition and structure of antelope communities in three study sites within the Niger Delta (Nigeria) based on bushmeat market data - Georgewill, I.; Akani, G.C.; Luiselli, L.; Petrozzi, F.; Dendi, D.; Ugbomeh, A.P.; Fa, J.E.; Onuegbu, G.C. (Springer, 2022)
The composition and structure of antelope assemblages were analyzed by using data from wild meat markets in three distinct study stations in the southern Niger Delta, Nigeria. The relative abundance of the different species coming into the markets was analyzed, and various diversity metrics were used to describe the different antelope communities. Sex ratios of these populations as well as the effect of season on the abundance of the various species in the markets were examined. It was observed that a single recently described species (Philantomba walteri) was the dominant species in the three localities, contributing about 70% of all the antelope individuals. The relatively low number of antelope carcasses observed in this study (less than the number of carcasses of small carnivores in the same sites) suggests that the ungulate fauna is already very depleted in the eastern Niger Delta region, with these mammals being hunted more intensely in the wet season.